Fully automated on‐screen carotid intima‐media thickness measurement: A screening tool for subclinical atherosclerosis. Issue 6 (28th March 2013) - Vanoli, Davide; Lindqvist, Per; Wiklund, Urban; Henein, Michael; Näslund, Ulf
ABSTRACT Purpose Carotid intima‐media thickness (CIMT) is generally considered an appropriate direct vascular method for cardiovascular risk assessment. The objective of this study was to evaluate the feasibility and reproducibility of a newly developed automated on‐screen carotid ultrasound with respect to manual measurement with a conventional system. Methods We assessed CIMT in 50 consecutive patients (age 62 ± 5 years, range 21–79 years, 36 men) twice, using a newly developed automated ultrasound (CardioHealth Station) and a conventional system with manual measurement (Acuson, Sequoia). For each patient, three frozen frames of the distal 10 mm of the right and left common carotid arteries were acquired on the two systems, by operators blinded to each other. The average of the mean value of three readings of each system was calculated. Results The intraclass correlation coefficient of the interoperator variability was 0.95 and 0.94 for the automated and manual measurements, respectively. The comparative coefficient of variation of the interoperator variability was 8.2 and 8.7% for the automated and manual measurements, respectively. There was no clinically relevant difference between measurements obtained by the two systems (intraclass correlation coefficient = 0.98). The acquisition time of the automated system was significantly shorter than the conventional system (p < 0.01). Conclusions Fully automated on‐screen measurements of CIMT are feasible, faster, and as reproducible as conventional manual measurements and may be suitable and cost‐effective for screening application in community medicine. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound41:333–339, 2013